PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN KERAJINAN TANGAN MACRAME DAN OPTIMALISASI PEMANFAATAN TEKNOLOGI INFORMASI UNTUK PEMASARAN PRODUK - Poppy Dian Indira Kusuma; Afiq Chamim Mubaroq; Ninda Dwi Safitri; Suci Indah Pratiwi; Syifa’ Ibnatu Sulaiman; Rr Puteri Aida Laily Inas (Jurnal Abdimas Bina Bangsa, 2024)
Poverty has been a problem for almost all countries. Efforts to reduce poverty can be done by increasing community capacity and productivity and creating new jobs. Family Welfare Empowerment (PKK) is a forum for society to increase its capacity and productivity. The main problem faced by the people of Karangnanas Village, Banyumas Regency is the lack of optimal empowerment of their resources, especially human resources. This Community Service Activity (PKM) aims to empower the community through macrame handicraft and social media optimization training for product marketing. These trainings are expected to increase the knowledge and skills of the community, as well as foster the entrepreneurial spirit of the people of Karangnanas Village. Optimizing marketing via social media is an important strategy in business. With advances in information technology, product sales will become more efficient and can reach a wider market. This PKM activities are carried out through 3 stages: preparation, training and practice, as well as evaluation. These PKM activities are expected to be sustainable and encourage people to become entrepreneurs which in turn will improve the welfare of the people of Karangnanas Village